2009
DOI: 10.3802/jgo.2009.20.3.137
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances of robotic surgery and single port laparoscopy in gynecologic oncology

Abstract: Two innovative approaches in minimally invasive surgery that have been introduced recently are the da Vinci robotic platform and single port laparoscopic surgery (SPLS). Robotic surgery has many advantages such as 3-dimensional view, the wrist like motion of the robotic arm and ergonomically comfortable position for the surgeon. Numerous literatures have demonstrated the feasibility of robotic surgery in gynecologic oncology. However, further research should be performed to demonstrate the superiority of robot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 54 publications
(31 citation statements)
references
References 42 publications
(45 reference statements)
0
31
0
Order By: Relevance
“…SPLS is a cutting-edge technology for minimally invasive surgery [12]. Although the single port laparoscopic approach has been used for tubal ligation since the 1970s and Ghezzi et al reported a successful salpingectomy using SPLS, the single port laparoscopic approach has not been widely used due to its technical difficulty [1,13].…”
Section: Commentsmentioning
confidence: 99%
“…SPLS is a cutting-edge technology for minimally invasive surgery [12]. Although the single port laparoscopic approach has been used for tubal ligation since the 1970s and Ghezzi et al reported a successful salpingectomy using SPLS, the single port laparoscopic approach has not been widely used due to its technical difficulty [1,13].…”
Section: Commentsmentioning
confidence: 99%
“…Homemade transumbilical port using Alexis wound Retractor®, glove and conventional laparoscopic trocars have been in use to perform various operations like varicocelectomy, transumbilical pre-peritoneal (TAPP) inguinal hernia repair, hemicolectomy and laparoscopic total hysterectomy [1][2][3].…”
Section: Discussionmentioning
confidence: 99%
“…It can also be performed using one of the many commercially available multichannel single-port devices: R-port™ (Advanced surgical concepts, Dublin, Ireland), Uni-X™ (Pnavel system, Morganville, NJ, USA), and SILS port™ (Covedien). Several successful general surgical, urological and gynaecologica procedures were also performed with a homemade transumbilical port using the Alexis wound retractor® and surgical gloves [1][2][3]. The commercially available multichannel single-port devices are very costly and Alexis wound retractor® is not available in this part of our country.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, some reports have demonstrated the feasibility and safety of SPLS and the improvement in outcomes over conventional laparoscopy in terms of pain, recovery time, cosmesis, and duration of hospital stay [5][6][7][8][9][10]. However, SPLS is not widely available due to the technical difficulty of the procedure.…”
mentioning
confidence: 96%